The Role of Temperament and Character with the Mediating Effect of Perceived Deception in the Formation of Dark Tetrad Personality Traits - Parsakia, Zahra; Zeinali, Ali (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The aim of research was determine the role of temperament and character with the mediating effect of perceived deception in formation of dark tetrad personality traits.Methodology: The present research was cross-sectional from type of correlation. The statistical population was all managers of the government offices of Tabriz city in 2024 year with number of 8280 people and the sample size was determined 420 people, which were selected by available sampling method. Data were collected by temperament and character questionnaire, perceived deception scale and dark tetrad personality traits scale and were analyzed with using Pearson correlation coefficients and structural equation modeling methods in SPSS and Smart-PLS software.Findings: The results showed that the model of temperament and character with the mediating effect of perceived deception in the formation of dark tetrad personality traits had a good fit. Also, the direct effect of temperament on perceived deception and dark tetrad personality traits was negative and significant, the direct effect of character on perceived deception was positive and significant and on dark tetrad personality traits was negative and significant and the direct effect of perceived deception on dark tetrad personality traits was positive and significant (P